Educational Inequalities Among Muslim Women in Janaki Rural Municipality-3, Banke, Nepal: A Socio-Cultural and Economic Analysis - Gautam, Jentil (Academia Research Journal, 2025)
Educational inequality remains a critical challenge in Nepal, particularly among marginalized communities such as the Muslim population. This study examines the socio-cultural, economic, and religious factors contributing to educational disparities among Muslim women in Janaki Rural Municipality-3, Banke District, Lumbini Province. Employing a mixed-methods approach, this research incorporated household surveys (n=42), key informant interviews (n=15), and focus group discussions (n=6) to analyze parental attitudes, economic constraints, and religious influences on girls’ education. The findings reveal that patriarchal norms, economic deprivation, and conservative religious interpretations significantly hinder Muslim girls’ school enrollment and retention. Statistical analysis demonstrates complete gender segregation in educational pathways, with 85.44% of boys attending government schools while 100% of girls are confined to religious madrasas. The study concludes with evidence-based policy recommendations for promoting gender equity in education while respecting Islamic values.